Bank Credit Agreement With Warranty Of Decree Appointment Of Civil Servants - Chairul - Insani (Jurnal Akta, 2020)
The relationship between the bank and the customer in the credit agreement with the guarantee of a Decree on the Appointment of Civil Servants begins with the arrival of the customer at the PT. Bank Rakyat Indonesia (Persero) Tbk, Palembang branch on working days and hours to provide complete requirements and fill in loan application forms that can be taken immediately at the PT. Bank Rakyat Indonesia (Persero) Tbk, Palembang branch. Then proceed with the bank conducting a field survey to ensure that the debtor is indeed a civil servant according to the data written by the debtor and an assessment of the potential debtor's ability to pay off his debt. And it ends with the disbursement of credit funds by banks to debtors for the loan ceiling of 60% of the employee's net salary according to the class / rank owned by the customer / prospective debtor. This research uses an empirical juridical approach. This method is used to obtain the truth in discussing existing problems and to see the application of a rule of law in society. The analysis is carried out descriptively which will describe, describe and reveal how the actual implementation of the credit agreement with the guarantee of Civil Servant Decree at PT. Bank Rakyat Indonesia (Persero) Tbk, Palembang branch. The efforts of the banking sector to secure credit with the guarantee of a Decree on the Appointment of Civil Servants who are problematic are based on fulfilling the requirements and completeness of the identity data of the prospective debtor, the second is the provision of a period for debt repayment where the period does not exceed 5 years, and finally, the submission of a guarantee for the Decree of the Appointment of Civil Servants, all of which must be original. Credit settlement with the guarantee of a Decree on Appointment of Civil Servants who defaults, namely, first, deliberation with the debtor to fulfill the element of good faith, if it has not been responded to, the first legal route will be taken through the judiciary, the second through KP2LN (State Receivables and Auction Management Office). If the debtor is a mutation, it is requested or confirmed in advance to the office / agency where the debtor works to transfer funds against credit repayments with the guarantee of a Decree on the Appointment of Civil Servants.